Urban climate change adaptation as social learning: Exploring the proc ess and politics - Fisher, Susannah; Dodman, David (Environmental Policy and Governance, 2019)
Responses to climate change that build on adaptive natural resource ma nagement conceptualise social learning processes as having the potenti al to form a key component of climate adaptation. Social learning proc esses represent a way of managing the inherent uncertainties and inter connectedness of adaptation issues through ongoing learning, iterative reflection, and change of responses over time. Although the theoretic al case is emerging for social learning as adaptation, there is limite d empirical evidence of how these processes play out as local governme nts engage in urban adaptation planning. This paper starts to address this gap by examining social learning processes in two cities in India . We show how the social learning processes interact with complex gove rnance contexts in the two cities and how evidence of outcomes is emer ging across individuals, networks, and systems. We go on to argue that there are several areas of social learning that need further theorisa tion to support its application in the urban context. First, theories of social learning need to allow for unequal power relationships to co ntinue to shape learning processes and take into account structural an d historical dynamics as well as relational forms of power. Second, th e way that scale is understood needs to be reopened as a point of anal ysis to understand how scalar concepts are used by actors to frame and locate problems and solutions rather than being understood as fixed a nd immutable.
Keywords: Climate change; India; Social learning; governance; urban planning